Design of hierarchical TS-1 zeolites using spray-drying for enhanced catalytic activity in cyclic carbonate formation - Gryn, Svitlana; Kurmach, Mykhailo; Yaremov, Pavlo; Shvets, Oleksiy; Alekseev, Sergei; Wintzheimer, Susanne; Mandel, Karl (Microporous and Mesoporous Materials, 2025)
Herein we report on the design of hierarchical zeolite supraparticles from hydrothermally-derived 100 nm TS-1 zeolite nanoparticles (NPs) by means of spray-drying. These supraparticles, with a large surface area (up to 678 m2/g), possess a biporous structure that is composed of zeolitic micropores (0.9–1.1 nm) and secondary mesopores. Depending on the synthesis conditions, it is possible to prepare supraparticles, formed by separate NPs and wide (50 nm) interparticular pores or by zeolitic NPs, tightly glued together by amorphous mesoporous titanosilicate. According to the UV–vis spectrometry data and FTIR studies of adsorbed pyridine, the active sites of “separated” supraparticles are presented mainly by Lewis sites associated with [TiO4] species isolated in the zeolite matrix, while “glued” supraparticles possess a significant fraction of [TiO5] and [TiO6] species. The supraparticles demonstrate sufficiently high catalytic activity in the industrially valuable two-stage synthesis of cyclic carbonate (4-phenyl-1,3-dioxolan-2-one) from styrene and carbon dioxide, in the presence of tert-butyl hydroperoxide as an oxidant and tetrabutylammonium iodide as a co-catalyst. We found that the selectivity to the target cyclic carbonate increased with an external specific surface area growth, probably due to the facilitated withdrawal of reaction products from the zeolite pores.
CRIS-Team Scopus Importer:2025-04-04
Keywords: Carbon dioxide; Catalysis; Cycloaddition; Hierarchical zeolites; Spray-drying; Supraparticles; TS-1; Zeolite nanoparticles